Acute bilateral phrenic nerve neuropathy causing hypercapnic respiratory failure associated with checkpoint inhibitor immunotherapy. (2021) - Srinivasan, M.; Taylor, A.M.; Long, G.V.; Herkes, G.; King, G.G.
Abstract: We present two cases of acute hypercapnic respiratory failure due to diaphragmatic dysfunction secondary to bilateral phrenic nerve paralysis, in patients who were receiving immunotherapy for melanoma. Bilateral diaphragmatic paralysis is an uncommon cause of acute or sub-acute hypercapnic respiratory failure which causes severe breathlessness, orthopnoea and potentially death. Immune checkpoint inhibitors are now standard of care in several solid organ malignancies. However, their use is associated with a risk of developing autoimmune toxicities, which includes mononeuritis. Our two cases demonstrate the potential difficulties in recognising acute hypercapnic respiratory failure and diagnosis of the rare disorder of bilateral diaphragmatic dysfunction, with consequent delays in appropriate management. The occurrence of this rare condition in association with checkpoint inhibitor immunotherapy suggests a possible autoimmune mechanism. Awareness that this rare cause of respiratory failure may occur in patients receiving checkpoint inhibitor therapy might facilitate earlier diagnosis and treatment.